Impact of preoperative arterial and venous diameter on achievement of the adequate blood flow in arteriovenous fistula for hemodialysis. Issue 3 (24th August 2020) - Gjorgjievski, Nikola; Dzekova‐Vidimliski, Pavlina; Trajcheska, Lada; Stojanoska, Ana; Selim, Gjulshen; Rambabova‐Bushljetik, Irena; Nikolov, Igor; Gjorgievska, Juija; Janevski, Zoran; Muharremi, Shkleqim; Dejanov, Petar; Spasovski, Goce; et al.
Abstract: An arteriovenous fistula (AVF) remains the best choice of vascular access (VA) for hemodialysis (HD). The aim of the study was to determine the factors associated with the achievement of adequate blood flow (BF) of AVFs at the 4th week after creation. Created AVFs in 63 patients with chronic kidney disease (CKD) stage 4/5 and CKD stage 5 on hemodialysis (CKD5D) were analyzed in a prospective study. Doppler ultrasound (DUS) was used for measuring the diameter of the radial artery, the brachial artery and the cephalic vein before AVF creation. The BF of AVF was calculated by DUS at the 4th week after creation and adequate BF was defined as ≥ 600 mL/min. The average age of patients was 61.31 ± 12.9 years. An adequate BF of AVF at the 4th week after creation was achieved in 43.54% of patients. The BF of AVF measured in male patients was significantly higher compared to the BF of AVF obtained in females (576.03 mL/min vs 375.12 mL/min, P  = 0.004). The diameter of the blood vessels with achieved adequate BF was significantly larger compared to the diameter of the blood vessels without adequate BF (radial artery: 2.45 mm vs 2.03 mm, P  = 0.000; brachial artery: 4.78 mm vs 4.06 mm, P  = 0.001 and cephalic vein: 3.12 mm vs 2.83 mm P  =  0.018). The gender and the diameter of the blood vessels before AVF creation were significantly associated with achievement of adequate BF of AVF at the 4th week of creation.